School Strategies in Realizing Student Wellbeing in Public Senior High School 1 Gorontalo (Journal of Pedagogical Inventions and Practices, 2022)
This study aims to 1) describe the school program in realizing student wellbeing in SMA Negeri 1 Gorontalo, 2) describe the strategies of principals and teachers in realizing student wellbeing in Public Senior High School 1 Gorontalo. The approach used in this study uses a qualitative approach with the type of case study research. Data collection techniques in this study using interviews, observation and documentation. As for the results in this study, there are several programs and strategies carried out to fulfill the aspects of having, loving, being, and health in realizing student wellbeing "in the school environment can make students well-being because Public Senior High School 1 Gorontalo implements environmental development programs, green schools, banks garbage, adiwiyata, 5S culture and habituation program, bullying prevention, decision making, class meeting, extracurricular, UKS, PMR and PKR.